Antimicrobial susceptibility of Neisseria gonorrhoeae in Zaire: high level plasmid-mediated tetracycline resistance in central Africa. Issue 2 (April 1992) - Van Dyck, E; Rossau, R; Duhamel, M; Behets, F; Laga, M; Nzila, M; Bygdeman, S; Van Heuverswijn, H; Piot, P
Abstract : OBJECTIVE--To determine the in vitro antimicrobial susceptibility of gonococcal strains isolated in 1988 among female prostitutes in Kinshasa, Zaire and to characterise strains with high level tetracycline resistance. METHODS--Minimal inhibitory concentrations of 8 antimicrobials were measured by agar dilution technique. Plasmid-profiles and serovars were determined. RESULTS--Two hundred and thirteen strains of Neisseria gonorrhoeae were tested of which 59% were beta-lactamase producers and an additional 21% showed intermediate or chromosomal resistance to penicillin (MIC = 0.5-8 mg/l). Eleven percent of the strains were resistant to the combination sulfamethoxazole-trimethoprim (MIC greater than 8 mg/l) and 57% of the isolates showed decreased susceptibility to thiamphenicol (MIC = 1-4 mg/l). All strains were sensitive to spectinomycin, norfloxacin and ceftriaxone and moderately sensitive to kanamycin. Chromosomal resistance to tetracycline was observed in 45% of strains (MIC = 2-8 mg/l). Ten percent were highly resistant to tetracycline (TRNG, MIC = 16-128 mg/l) and were shown to carry a plasmid borne Tet M determinant; such strains were not found in Kinshasa in 1985. TRNG belonged to 4 different serovars, which were also the dominant serovars in non-TRNG. CONCLUSION--These findings illustrate the high frequency of multiresistant gonococci in Zaire and suggest that high level tetracycline resistant strains of N. gonorrhoeae have become endemic in Central Africa.